Estimação da seção em falta e processamento de alarmes em sistemas de potência utilizando um sistema híbrido fundamentado na heurística construtiva e na programação inteira - Fritzen, Paulo Cícero (2012)
This work proposes a methodology which is able to accomplish alarms processing and to estimate fault section in electrical power systems. The purpose is to filter alarms generated during a shutdown and indicate which equipment is at fault. To solve this problem, the methods employed are Constructive Heuristic (CH) and Integer Programming (IP) through their integration. Initially, CH method performs an analysis of fault direction in each power system equipment through alarms signaled by protective relays and circuit breakers status. Thus, by having as much information as possible, CH carries out an analysis on the level of equipment (busbars, power transformers and transmission lines) which can or cannot identify the direction in which disturbance occurred. The final processing is performed by IP, which analyzes the response of protection system as a whole (system-level analysis), using post-fault topology of power grid along with response of CH, indicating the fault section (s) and possible failures in the opening of circuit breakers.